1977
DOI: 10.1055/s-0028-1091503
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Involvement in Congenital Myotonic Dystrophy

Abstract: Dysfunction of smooth muscles is not unusual in adults suffering from myotonic dystrophy but has not yet been reported in patients with the congenital form of the disease. Of two brothers, the younger one presented with the typical features of congenital myotonic dystrophy at birth. He developed severe constipation due to megacolon during his second year of life. In the older brother disturbances of gastrointestinal motility, causing repeated bouts of subileus during the newborn period, sprue-like symptoms dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…It is unknown which part of this organ is mainly affected in CMyD, but the muscle layer is likely responsible to its dysfunction. It may be informative that in electron microscopic studies, the only abnormality in the appendix specimens from the CMyD patient with constipation owing to poor peristalsis was widely spaced smooth muscle cells 8 . Such an abnormality would be responsible for the alteration in the contractility of bile canaliculi and bile ductules, possibly leading to incomplete biliary obstruction and impaired bile excretion 9 .…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown which part of this organ is mainly affected in CMyD, but the muscle layer is likely responsible to its dysfunction. It may be informative that in electron microscopic studies, the only abnormality in the appendix specimens from the CMyD patient with constipation owing to poor peristalsis was widely spaced smooth muscle cells 8 . Such an abnormality would be responsible for the alteration in the contractility of bile canaliculi and bile ductules, possibly leading to incomplete biliary obstruction and impaired bile excretion 9 .…”
Section: Discussionmentioning
confidence: 99%
“…6 An interesting model that may explain such clustering of apparently rare complications was recently proposed by Beggs et al,"2 who found deletions in the dystrophin gene in three out of 23 patients with a clinical diagnosis of Fukuyama congenital muscular dystrophy (FCMD). They suggested that the FCMD phenotype in these patients could be explained on the basis of an interaction of heterozygosity for FCMD and hemizygosity for the dystrophin mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Otras hipótesis sugieren una deficiente inervación del músculo liso, infiltración grasa de las paredes de las vísceras huecas, fibrosis de estas paredes o, incluso, degeneración del músculo liso. Para estas hipótesis no hay, sin embargo, estudios concluyentes [90][91][92][93] .…”
Section: Afectación Gastrointestinalunclassified